'Healthy on Hormones': improving the experience of men with advanced prostate cancer. Issue 1 (7th July 2014) - Fleure, Louisa
ABSTRACT Long‐term androgen deprivation therapy (ADT) for advanced prostate cancer can result in significant and distressing side effects and longer‐term adverse metabolic effects. A seminar‐based service improvement initiative was developed to provide information and strategies to understand ADT, to manage side effects and to provide lifestyle advice regarding cardiovascular and bone issues. The seminars were evaluated with patient questionnaires and were positively received. This approach has proven to be a valuable tool in the care of this patient group.